2006
DOI: 10.1158/1078-0432.ccr-06-1140
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between High Vascular Endothelial Growth Factor-A Serum Levels and Treatment Outcome in Patients with Standard-Risk Acute Lymphoblastic Leukemia: A Report from Children's Oncology Group Study CCG-1962

Abstract: Purpose: Many molecular pathways, including cell cycle control, angiogenesis, and drug resistance, mediate tumor growth and survival. Vascular endothelial growth factor-A (VEGF-A) serum levels <40 and >100 pg/mL have been associated with good and poor prognoses, respectively. Experimental Design: The hypothesis was that serum VEGF-A levels in standard-risk acute lymphoblastic leukemia pediatric patients at induction are predictive of event-free survival (EFS). One hundred seventeen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 51 publications
2
21
2
Order By: Relevance
“…However, we did not observe significantly worse OS, suggesting that some of the relapsed patients might have responded to salvage therapy. Our findings are consistent with previous observations that elevated VEGF is associated with worse outcomes in patients with hematologic malignancies after chemotherapy [14-16] and that increased pretransplant VEGF levels are associated with higher rate of relapse and worse PFS after allogeneic HSCT from adult donors [17]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, we did not observe significantly worse OS, suggesting that some of the relapsed patients might have responded to salvage therapy. Our findings are consistent with previous observations that elevated VEGF is associated with worse outcomes in patients with hematologic malignancies after chemotherapy [14-16] and that increased pretransplant VEGF levels are associated with higher rate of relapse and worse PFS after allogeneic HSCT from adult donors [17]. …”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the mandatory role of VEGF-mediated angiogenesis in hematopoiesis, VEGF blockade at the time of transplantation in lethally irradiated mice results in failure of hematopoietic reconstitution and early death [9]. Elevated levels of VEGF and/or its receptors have been reported in patients with hematologic malignancies, where they play a role in an autocrine/paracrine fashion [10-12], and have been shown to be of prognostic significance [13-16]. Levels of VEGF before allogeneic HSCT are associated with increased risk of relapse [17], but reports regarding its role on clinical outcomes such as graft-versus-host disease (GVHD), nonrelapse mortality (NRM), or survival are conflicting [17-20].…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al demonstrated a novel mechanism in which lovastatin inhibits both ligand-induced VEGFR-2 activation through inhibition of receptor internalization and VEGF activation of PI3K/AKT pathway in endothelial cells [72]. Since angiogenesis has a central role in clinically aggressive hematologic malignancies such as nonHodgkin lymphomas [73][74][75], angioimmunoblastic T-cell lymphoma [76,77], ALL [78], AML [79], and multiple myeloma [80], inhibition of the VEGF-mediated intracellular signal via bevacizumab could be further facilitated by blocking the mevalonate pathway.…”
Section: Inhibition Of Angiogenesismentioning
confidence: 99%
“…High serum VEGF levels have also been associated with poor prognosis in certain leukemias (5). Accordingly, one study has shown that standard-risk pediatric patients with ALL who have high VEGF levels after induction therapy relapse earlier than those with low levels (6).…”
Section: Introductionmentioning
confidence: 99%